Modified Series-Parallel Photovoltaic configuration to Enhance Efficiency Under Partial Shading - Jubaer Ahmed; Hadi Nabipour-Afrouzi; Mohammad Faridun Naim Tajuddin (International Journal of Integrated Engineering, 2019)
Partial shading is a phenomenon where photovoltaics (PV) array experiences irregular level of irradiances. Such mismatch can cause a significant reduction in power yield. To mitigate the effect of partial shading, PV modules in an array are connected in various configurations namely Series-Parallel (SP), Total-Cross-Tied (TCT), Bridge-Linked (BL) and Honey-Comb (HC) etc. However, all these techniques introduce redundancy and complexity while improving the performance by very little. In this paper, a new PV configuration is proposed to solve the limitations of the existing PV configurations. The proposed configuration is a modified version of SP, hence referred as MSP configuration. To justify the performance of the proposed scheme, several experiments have been carried in MATLAB Simulink. Total 14 partial shading cases are simulated to compare the output performance between generic SP and proposed MSP configuration. The proposed MSP configuration is validated to be superior compared to normal SP configuration under majority of the cases. Depending on shading pattern, the efficiency of the PV array can be enhanced up to 37%, if MSP configuration is implemented.